The impact of health and technology shifts on antibiotic use among the elderly in Thailand - Nakarin Prasit; Surachai Phimha; Ampawan Nonthamat; Nathakon Nilnate; Nattaporn Nidthumsakul; Puwanart Sresutham (Scientific Reports)
Abstract The utilization of antibiotics among the geriatric population in Thailand has been markedly influenced by the COVID-19 pandemic. This investigation sought to analyze the correlation between antibiotic utilization and determinants such as pharmacy density, healthcare workforce, household internet accessibility, and income during the period of 2021–2023. A spatial examination employing panel regression was performed on data derived from Thailand’s National Statistical Office Health and Welfare Survey 2023, encompassing all 77 provinces. The research scrutinized antibiotic usage trends among individuals aged 60 and above, associating them with diverse socioeconomic and healthcare access metrics. Notable spatial and temporal variations in antibiotic utilization were detected. The physician ratio demonstrated a negative association with antibiotic usage (Coefficient=− 0. 613, P = 0.035), while household internet accessibility showed a positive relationship (Coefficient = 0.003, P = 0.001). Household income exhibited a slight negative effect (Coefficient=− 0.0002, P = 0.024). No statistically significant associations were found between antibiotic usage and pharmacy density or nurse ratio. The study clarifies complex interrelations between healthcare accessibility, socioeconomic determinants, and antibiotic usage among the elderly in post-COVID-19 Thailand. These results indicate the necessity for targeted interventions to foster judicious antibiotic utilization, including enhancements in healthcare accessibility, the development of dependable digital health infrastructures, and the execution of income-sensitive health education initiatives.